PERBANDINGAN BIAYA DAN WAKTU ANTARA METODE KONVENSIONAL DENGAN METODE MODULAR MENGGUNAKAN MICROSOFT PROJECT - Huwaida, Nabila Yusriyya; Handayani, Fajar Sri; Rifai, Muji (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2024)
Indonesia's construction sector is experiencing rapid growth, this proven by numerous development projects, including a sub-district building construction project, aiming to optimize community services. A project must have three aspects, namely cost, quality and time. Choosing an implementation method is very important so that a project can achieve these three goals. The research method used a quantitative descriptive approach with the aim of comparing cost and time aspects between conventional methods and modular methods. The conventional approach involves working on site using conventional building materials, while the modular approach involves the use of pre-fabricated modules. In analyzing the costs and time of construction of the Grabag Sub-district office building, Purworejo Regency, Microsoft project application was used to calculate the duration of the work. The cost analysis show that building structure work using the conventional method costs Rp.3,086,929,413.11, while the modular method costs Rp.3,646,018,620.52. So the difference in the cost of construction work is Rp.559,089,207.42 or 18.11% higher for work using the modular method. The time analysis obtained building structure work using conventional methods require 150 days while the modular method is 87 days or time efficiency of 63 days or 42% lower for work with modular methods. The results of the Time Cost Trade Off (TCTO) calculation showed that the total project cost for conventional construction was Rp.2,781,017,489 while the cost for modular construction was Rp.3,117,530,328. So a difference of Rp.336,512,839 is higher for modular construction. Therefore, conventional construction is the most economical option for the sub-district building.